The Effect of Nutritional Status and Parental Income Level on the Incidence of Pulmonary Tuberculosis in Toddlers in the Working Area of the Manduamas Health Center, Central Tapanuli Regency - Yohana Tetty Gultom; Lisnawati Tumanggor (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Nutritional status is one of the risk factors that can cause the incidence of tuberculosis. The income level of parents has a close relationship with economic status and will indirectly make TB transmission easier. Tuberculosis is an infectious disease that attacks the lungs and is caused by bacteria (Mycobacterium tuberculosis). This study aims to determine the relationship between nutritional status and parental income level to the incidence of pulmonary TB. This type of research is quantitative with a case control approach, the sample calculation in this study uses the total sampling technique using inclusion and exclusion criteria so that a sample of 17 controls and 17 cases is obtained. Then anthropometric measurements and interviews were carried out with parents of toddlers. Univrriat and bivariate analysis were carried out using the chi square test, with the help of SPSS 25.0 with p = 0.05. Based on the results of the study, the p value < 0.05 is the variable of TB/U nutritional status (p-value = 0.039, OR= 4.4, CI= 1.041-18.599). It is recommended to the Nutrition Officer of the Puskemas to increase the activity of screening nutritional status in children under five.